"Failure" Irrelevant: Virtual Schools and Accountability-Immunity. Issue 7 (July 2016) - Nespor, Jan; Voithofer, Rick
Background: Virtual schools—free, state-funded, credit-awarding elementary and secondary schools offering curricula and programs exclusively online—are a rapidly expanding sector of U.S. education. Some of the largest of these schools have low graduation rates and receive "failing" rankings on state accountability metrics. They nonetheless flourish and grow, seemingly immune to sanctions that would be applied to traditional schools with similar ratings. Purpose: Taking one of the largest virtual schools in the United States, Ohio's Electronic Classroom of Tomorrow (ECOT), as a paradigmatic case, we examine how such immunity is produced. Findings: The ECOT case requires us to problematize standard educational categories. Unlike the schools presupposed in state accountability systems, it stretches across an evolving set of integrally connection organizations and actors that together form something that is a public school, but also a for-profit business, a political actor, and a technology infrastructure. Drawing on a set of "analytic tactics, " we analyze this form as an "assemblage" composed of multiple facets or "avatars" whose relations and boundaries change over time. Some avatars can generate profits, others are nonprofit; some are political actors that can influence their regulatory environments, other are barred from political activity; one avatar is confined to Ohio, another can move across state lines. Each avatar is legible to the state in terms of a different accountability regime. The way the state "sees" and assesses the assemblage as a whole depends on which avatar it focuses upon. Implications: The case complicates standard notions of school and accountability by pointing to the multiplicity of state accountability frames and the abilities of certain assemblage forms to influence how the state sees them. It also raises issues of how new territorial configurations of schools (their expansion to the level of the state) are linked to policy agendas in and out of education. Finally, it contributes to our understanding of policy networks by pointing to ways that assemblage forms allow entities like the one ECOT is part of to extend themselves in space and time, generate new organizational forms, and mobilize political capital. Virtual schools—public schools offering programs, and awarding credits and credentials exclusively online—are a small but rapidly growing sector of American education. The largest of these schools, managed by for-profit educational management organizations (EMOs), prosper with strong political support at the state level, despite receiving poor "grades" on state evaluation measures and graduating fewer than half their students. This article examines how such a school can flourish, seemingly immune to consequences, with ratings that would normally bring penalties to traditional schools. We examine the case of the Electronic Classroom of Tomorrow (ECOT). With over 15, 000 students, ECOT is the largest virtual school in Ohio, a state with one of largest population of virtual school students in the United States. ECOT receives failing or "F" grades on state ratings and graduates around 40% of its students. Nevertheless, its enrollments grow, it retains political support, and its funding and operating revenues continue to rise. ECOT is not typical of online education. Rather, it is a paradigmatic case of the category of large, EMO-managed schools that account for most virtual school enrollments nationally. Like ECOT, these other large, EMO-run schools receive poor ratings and have low graduation rates, yet seem resistant to state sanction. In ECOT's case, school officials defend its performance by arguing that most of its students come from low-income backgrounds and arrive with histories of academic failure, and that ECOT performs no worse than these other schools, and does so at less cost. Critics argue the school's immunity has more to do with large political contributions made to state political campaigns by its founder and others associated with the EMO. Both accounts are inadequate, and gloss over the more fundamental institutional transformations implied by ECOT. Standard school categories, we suggest, are inadequate for analyzing these transformations, so we draw on a pair of provisional concepts, assemblage and avatar. By assemblage (a term now common in policy studies) we mean relationally constituted networks of people, texts, technologies, and organizations—but networks in which the links connecting elements are understood to be alive, forming, breaking, and reforming ties, in the process moving, hardening, or dissolving boundaries, and transforming the functions of the elements. Avatar is a borrowed term, taken from gaming and virtual reality literatures, where it refers to a representation or artificial persona that allows participation in different sociotechnical "worlds." Here we use it to refer to the ways facets of an assemblage, although inseparably and integrally meshed with its other elements, can be treated by the state as legally, organizationally, and financially distinct, with each facet subject to a different system of accountability. When the state focuses on one facet instead of the whole, that facet becomes the functional avatar of the assemblage, the form in which it is legible to the state. The body of the paper tracks the development of assemblage of which ECOT is a facet, from the school's founding to the present day. First, we describe the doppelganger inception of the assemblage as both school and business, and explicate how the business facet enables the assemblage to do things—accumulate profit, for example—that the public school alone cannot. The next section shows how, within a few years of its creation, the assemblage becomes a significant political actor at the state level, with a capacity to influence its political environment. We then track how the assemblage then translates itself into the form of a software technology, grows a new organizational shell (a new facet) around that technology, and expands beyond state borders. ECOT's evolving position in this assemblage makes it, at once, a school, a business, a political actor, and a software infrastructure. ECOTs resistance to sanction has its sources in this reconfiguration of the school into something unlike what we traditionally understand schools to be. Our answer to the question of how ECOT thrives, even when it fails by the terms of established school accountability regimes, is thus that it is not a school in the sense presupposed by those regimes. Rather, it is part of an evolving assemblage that redistributes core "school" functions—instructional program selection, hiring decisions, strategic planning, and so on—and adds new functions, across multiple avatars. This supplies one solution to the puzzle: Different avatars are legible to the state in terms of different accountability regimes. The assemblage looks better to the state as a business than as a school, it speaks louder as a political actor, it moves farther and combines better with other corporations as a software platform. By shifting avatars, the assemblage as a whole can slip across regulatory environments and influence how it held accountable by the state. The article concludes by examining some of the political implications and possibilities created by the rise of such assemblage form.